Codification, Technology Absorption, and the Globalization of the Industrial Revolution - Réka Juhász; Shogo Sakabe; David E Weinstein (The Quarterly Journal of Economics, 2026)
Abstract This article examines the global adoption of technology in the late nineteenth century. We construct several novel data sets to test the idea that the codification of technical knowledge in the vernacular was necessary for countries to absorb the technologies of the first Industrial Revolution. We find that comparative advantage shifted to industries that could benefit from these technologies in countries and colonies with access to codified technical knowledge, but not in other regions. Using the rapid and unprecedented codification of technical knowledge in Meiji Japan as a natural experiment, we show that this pattern emerged only after the Japanese government codified vast amounts of technical knowledge. Our findings shed new light on the frictions associated with technological diffusion and offer a novel explanation for why Meiji Japan was unique among non-Western countries in successfully industrializing during the first wave of globalization.